Needs and Challenges of School Counsellors in Puberty Counselling for Girls - Laleh Tajadiny; Zohreh Khoshnood; Masumeh Ghazanfarpour; Atefeh Ahmadi (International Journal of School Health, 2024)
Background: Puberty is an important period that requires proper guidance for a safe transition to the next stage of development. The role of school counselors is crucial in guiding students as they face challenges and complexities during counseling. The present study aimed to assess needs and challenges faced by school counsellors in providing puberty counselling for girls.Methods: A descriptive-analytical cross-sectional design was used in this study. A total number of 132 school counsellors were selected using the convenience sampling method from the girl’s high schools of Kerman Province, Iran in 2020. A researcherdesigned questionnaire was used to collect data. Mean and standard deviation, non-parametric tests, such as Mann-Whitney, Kruskal-Wallis, and Spearman correlation coefficient tests of SPSS version 22 were used for data analysis.Results: The mean age of the study participants was “43.75±6.94” years. Results showed that most of the counsellors agreed with the “need for specialized education for counsellors on an international level and based on new sciences” “(94.7%)”, while most disagreed with “not adhering to professional ethics in counselling” “(69.7%)”. Additionally, the highest total mean was attributed to the “inadequate skills in counselling” “ (M±SD=24.67±16.78)”, indicating high disagreement, and the lowest mean was attributed to “financial and human resources limitations” “(M±SD=4.87±4.2)”.Conclusions: The study results showed that there is a necessity to implement strategic measures to enhance the quality of counseling services and elevate the status of school counselors. A thorough understanding of counselors’ expertise is essential for them to utilize their skills efficiently and boost their effectiveness. Thus, it is recommended that future research includes interventions aimed at furthering the training of school counselors.